Seismic Performance of Precast Concrete Special Moment Frames with Hybrid Connection System in Five and Ten Story Buildings - Jimmy Chandra; Vito Nathaniel Lokito; Jonathan Aurelius Tambuna (Institute of Research and Community Outreach - Petra Christian University, 2023)
Precast concrete has been widely implemented in various construction projects due to shorter construction duration and consistent quality. In a previous study, Solberg et al. (2008) conducted an experiment on hybrid beam-column connections with Damage Avoidance Design concept to improve the seismic performance of precast concrete special moment frames. The objective of this study is to further evaluate the seismic performance of precast concrete special moment frames with the hybrid beam-column connections in five and ten story buildings. The evaluation was done through non-linear dynamic time history analysis using OpenSees. The analysis results show that precast concrete frame buildings exhibit insignificant difference in maximum interstory drift ratios and roof displacements as compared to conventional concrete frame buildings. However, with significantly smaller residual displacements which indicates less structural damage, precast concrete frame buildings could be preferred in the long run as they require less structural repairs after a strong earthquake event.